Immunohistochemical features of the fallopian tubes’ structure in case of fetuses with a gestational term of 21-28 weeks from mothers with a chronic infection of the lower genital tracts - Poliasnyi, V.; Kupriianova, L. (Journal of Education, Health and Sport, 2021)
In the following article we are disclosing immunohistochemical features of the fallopian tubes’ structure in case of fetuses with a gestational term of 21-28 weeks. We have studied the structure of organs of 15 fetuses from mothers with a chronic infection of the lower genital tracts (HILGT) (the group of comparison) relatively to one in case of 15 fetuses from mothers with a physiological pregnancy (the main group). All fetuses had a gestational term of 21-28 weeks and had died intranatally as a result of an acute disorder of uterine-placental circulation. Methods of reearch: organometric, histological, immunohistochemical and statistical. The complex research allowed to reveal a probable decrease of the organometric data as well as indicators of thickness of the main structural components of the organs’ wall in case of fetuses from mothers of the group of comparison relatively to ones in case of fetuses from the main group. By applying histological method we had reveled a disorder in the strucuture of mucous and muscular membranes in the structure of organs of fetuses from mothers with a pathology of pregnancy, which is manifested by decreasing of number of folds, uneven thickness of the mucous membrane as well as disorder in formation of the muscular membrane’ layers. Immunohistochemical method has revealed an increase of apoptotically changed mucosal cells in the fallopian tubes of fetuses from mothers with HILGT. By applying MCAT to endotheline-1 we have revealed an increased glow of endithelial cells in vessels both of arterial and venous types in the strucuture of the organs’ wall in case of fetuses from the group of comparison. During the study on the endocrine activity of organs of fetuses from mothers with complicated pregnancy we have postulated a probable decrease of the cells’ glow’ intensity towards MCAT of progesterone. At the same time, there is also an inflammatory infiltration in the mucous membrane of the fallopian tubes’ wall. The aforementioned changes in the strucuture as well as in the functional activity of fetuses’ organs from mothers’ with HILGT are formed under the influence of chronic hypoxia and endocrine insufficiency of the feto-placental complex, which is taking place in case of this pathology. Histological and immunohistochemical features of the fallopian tubes’ structure in case of fetuses from mothers with complicated pregnancy are indicating a disorder in formation and maturing of the organ as well as they could lead to development of ectopic pregnancy and tubal infertility in the subsequent ontogenesis.